Effects of Different Physical and Chemical Parameters on Phosphate Solubilization Activity of Plant Growth Promoting Bacteria Isolated from Indigenous Soil - Talat Yasmeen Mujahid; Syed Abdus Subhan; Abdul Wahab; Javeria Masnoon; Nuzhat Ahmed; Tanveer Abbas (Journal of Pharmacy and Nutrition Sciences, 2015)
The microorganisms play a vital role in fertility of soil and hence favors’ large group of plants. In present study we have successfully isolated certain bacteria from soil including both Gram positive and Gram negative bacteria and access their ability in phosphate solubilization. Effects of temperature, pH and different carbon sources, on phosphate solubilization, by these isolates were also determined. Low temperature 25 °C, pH between 5-7, and glucose as carbon source were found to be best for phosphate solubilization by most of the isolates. Present study highlights the importance of these plants growth promoting bacteria and their uses for agriculture purposes.